Uncovering Research Trends in Safety Culture in the Global Construction Industry: A Bibliometric Analysis (1995-2020) - Otitolaiye, Victor Olabode; Ubana, Dodeye O.; Palathoti, Suvarnaraju; Otitolaiye, Adekunle Donald (International Journal of Occupational Safety and Health, 2022)
Introduction: Safety culture has mainly been used across several safety management literatures to describe the level of safety within workplaces. This paper presents the research landscape and scientific developments on safety culture in the global construction industry. Methods: The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) approach was employed to identify, screen, and analyze the published documents indexed in the Elsevier Scopus database. Next, the research landscape and scientific developments on the topic were examined by bibliometric analysis (BA) through co-authorship, keywords co-occurrence, and citations. Results: Results showed that 738 documents were published and indexed on the topic between 1995 and 2020. The findings showed that articles are the preferred medium, whereas Engineering is the preferred subject theme for published documents on the topic. The journal of Safety Science (published by Elsevier) is the most influential source of publications on the topic. In contrast, Dongping Fang, based at Tsinghua University (China), is the most influential researcher due to the substantial research grants and financial support from the National Natural Science Foundation. Further analysis showed that the most prolific authors on the topic are based in China, Australia, and Indonesia, although the United States has published the most documents. BA also revealed large networks of researchers and co-occurring keywords and the organizations and countries that currently exist, collaborate, and cite each other works on the topic. Conclusion: The findings indicate that safety culture in the global construction industry has undergone significant scientific developments resulting in high research impact mainly due to its role in preserving the health and safety of workers.